(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
This study examines the integration of practical experimental methods into the Thermodynamics and Fluid Mechanics course for students specializing in Ship Electrical Equipment, focusing on understanding hydrostatic pressure in liquids. Using the HM 150.05 experimental unit, available in the Applied Mechanics Laboratory, the research aims to bridge theoretical knowledge with practical application. The experiment not only reinforces key principles linking thermodynamics and fluid mechanics but also provides students with a tangible understanding of the forces acting in the marine environment. The results highlight the effectiveness of experimental analysis in enhancing student comprehension and engagement.